Dampak Kecanduan Game Online Terhadap Prestasi Belajar Mahasiswa IAIN Syekh Nurjati Cirebon - Adji Firmansyah; Septi Gumiandari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The development of technology is currently increasingly rapidly providing convenience and benefits for humans, one example of technology that provides entertainment benefits is online games. However, online game addiction is one of several forms of addiction caused by technological developments, one of which is the internet or better known as internet addictive disorder. The objectives of this research are: 1) Analyzing online game addiction experienced by students IAIN Sheikh Nurjati Cirebon. 2) Analyze the learning achievements experienced by IAIN Syekh Nurjati Cirebon students. 3) Analyzing the influence of online games on the learning achievement of IAIN Syekh Nurjati Ciebon students. This research uses descriptive qualitative methods. The data collection technique applied in the research was interviewing 5 students and distributing questionnaires which were filled in by 15 students. The results of this study show 1) Most respondents (50%) had difficulty stopping playing online games, while 33.3% admitted that they had fairly good control but still felt interested in continuing to play. 2) Effective learning can help pupils and students to achieve learning goals. 3) It can be concluded that 37.5% stated that they do not like playing online games, because they have a very bad effect on learning. In the same percentage, 37.5% stated that they did not agree with online games, but did not provide clear reasons. It can be concluded that the research shows that the majority of respondents have difficulty stopping playing online games, while effective learning can help achieve learning goals, and around 37.5% of respondents stated that they do not like or disagree with online games because they have a bad effect on learning, although some of them they didn't give a clear reason.